Supporting Social Accountability in the Middle East and North Africa : Lessons from Transitions - Bousquet, Franck (World Bank, Washington, DC, 2012)
Social accountability is increasingly recognized as a way to make governance reforms and development efforts more effective in responding to the needs of citizens. Supporting initiatives that strengthen social accountability at the regional and national levels is consistent with the priority the Bank places on social and economic inclusion, citizen participation, and the quality of governance. The longer paper provides a brief overview of some experiences in the Middle East and North Africa (MNA) Region and international experiences from Indonesia, Turkey and the Philippines supporting social accountability during political and economic transitions. The full paper was prepared for a conference around the 2011 Annual Meetings in Washington, DC and included high-level policy makers from Egypt, Tunisia, Turkey, Indonesia and the Philippines. A panel of civil society organizations from the MNA Region exchanged perspectives about social accountability in the region, emerging opportunities and remaining challenges in making government more effective through an informed and engaged citizenry.